Influence of Vitamin K on Bone Mineral Density and Osteoporosis - Elshaikh, Abeer O (Cureus, 2020)
Vitamin K (VK) has an established biological function in blood coagulation and hemostasis and maintains general health and bone wellbeing. VK supplements have been promoted to treat and prevent many diseases, particularly for decreasing fracture risk in osteoporosis, a chronic condition described by weak bone tissue, and a high fracture risk following minor trauma. It affects older people from different races and ethnicity, mainly postmenopausal women. Many kinds of research emphasize the role of VK in improving bone health and preventing osteoporotic bone fracture, but the findings are mostly inconclusive. In this literature review, PubMed and Google Scholar databases were used as the primary sources to select the relevant studies and review the association between VK and bone health and also, to explore the impact of VK supplementation in osteoporosis management. A majority of studies reported that VK has an essential role in promoting bone health. Although some studies revealed that VK might increase bone mineral density and reduce fracture risk in people with osteoporosis, VK supplements' potential benefits were not sufficiently supported. Thus, more clinical studies are needed to determine the positive effects of VK supplementation in osteoporosis prevention and treatment.